2016
DOI: 10.17795/nmsjournal31624
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Peer Education and Orientation Tour on Anxiety in Patient Candidates for Coronary Angiography

Abstract: Background: Coronary angiography is a stressful procedure for most patients. The physiological responses caused by anxiety during coronary angiography increase the likelihood of dysrhythmia, coronary artery spasm, and rupture. Objectives: This study compared the effects of peer education and an orientation tour on anxiety in patients who were candidates for coronary artery angiography. Patients and Methods: This single blind quasi-experimental study was conducted in 2014. A total of 177 patients who were candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Moreover, the results of this study showed that after the training of home care, the rate of heart rate, respiratory rate, and systolic and diastolic blood pressure of the intervention group decreased significantly, this finding indicates a positive effect of home care training on heart rate, respiratory rate and systolic and diastolic blood pressure in patients with coronary artery disease. This finding is consistent with the results of a study by Farsi et al (2015) that showed the effectiveness of peer education and orientation tour on patients' the hemodinamic indices (19). The study of Orujlu et al (2014) has also shown that nurses' educational interventions have been effective in reducing the vital signs of endoscopic candidate patients (20), which is consistent with the findings of this study, But this finding contradicts the results of a study by Maguire et al (21) and García Sierra et al (22), This difference may be due to differences in the study population.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the results of this study showed that after the training of home care, the rate of heart rate, respiratory rate, and systolic and diastolic blood pressure of the intervention group decreased significantly, this finding indicates a positive effect of home care training on heart rate, respiratory rate and systolic and diastolic blood pressure in patients with coronary artery disease. This finding is consistent with the results of a study by Farsi et al (2015) that showed the effectiveness of peer education and orientation tour on patients' the hemodinamic indices (19). The study of Orujlu et al (2014) has also shown that nurses' educational interventions have been effective in reducing the vital signs of endoscopic candidate patients (20), which is consistent with the findings of this study, But this finding contradicts the results of a study by Maguire et al (21) and García Sierra et al (22), This difference may be due to differences in the study population.…”
Section: Discussionsupporting
confidence: 93%
“…Evidence shows that patients scheduled for coronary angiography often experience anxiety, stress, and depression [2,3]. Furthermore, having sufficient information about this invasive procedure can help control vital signs including systolic blood pressure, diastolic blood pressure, and the heart rate in patients awaiting coronary angiography [4,5]. According to the literature, mobile phone-based patient education can decrease the anxiety of patients scheduled for coronary angiography [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…[41] There are different diagnostic techniques for evaluating cardiology patients, including catheterization being most frequent radical technique for cardiac disease detection. [39] As in United States, about 2 million people die every year [42], or above 260,000 in Iran experience diagnostic coronary angiography and intervention therapy or even both [43]. Risks in surgical procedures such as fatalities, MI, cerebrovascular accident, myocardial perforate, circulatory expansion, and regional myocardial channel issues were typical in screening and segmental treatment techniques which are performed via veins access.…”
Section: -Parisha Rai Et Al (2019)mentioning
confidence: 99%